Active Behaviour in Structure of Spirituality of Personality in Students - A V Ivashchenko; T V Chkhikvadze (Peoples' Friendship University of Russia (RUDN University), 2013)
The article is devoted to the gender peculiarities of spirituality manifestation and activity in the students of the PFUR.